REGULASI EMOSI SEBAGAI PREDIKTOR RESILIENSI PADA IBU TUNGGAL YANG DITINGGAL PASANGAN KARENA KEMATIAN - Shema Christy Noya Simamora; Krishervina R. Lidiawati (Jurnal Psikologi, 2023)
Single mothers have difficult conditions that can trigger emotional experiences, such as supporting their own families, energy and time constraints, negative views of society, and the vulnerability of single mothers as women in terms of emotions. This makes it thought that single mothers need to have the ability to survive and have the quality to bounce back during the condition by regulated emotions. The study aims to explore the influence of emotion regulation, specifically cognitive reappraisal and expressive suppression strategies, in helping single mothers increase resilience. The study used quantitative research methods, with the Emotion Regulation Questionnaire and Connor-Davidson Resilience Scale 25 items. The results found that there was a significant influence between both emotional regulation strategies on single mother resilience, with cognitive reappraisal strategies exerting a greater influence. Single mothers need to practice expressive suppression emotion regulation strategy skills, so that single mother resilience can be more optimal when single mothers are able to apply each emotional regulation strategy adaptively to their difficult conditions.